Examining the link between Spiritual Values at Work, Learning Orientation, Human Resources Practices and Organizational Health: An Indonesia Case Study - Ikhwan, Ikhwan; Sudiro, Achmad; Noermijati, Noermijati; Rahayu, Mintarti (International Review of Management and Marketing, 2017)
The purpose of this paper is to present an in-depth analysis of the spiritual values at work(SVW) and its inï¬‚uence on learning orientation (LO), human resources management practices (HRP) and organizational health (OH) in the financial sector.The foundations of SVW, LO, HRP and OH were assessed using a validated questionnaire. A total of 139 branch manager from the Indonesian financial sector participated in the survey. Partial least square structural equation modeling (PLS-SEM) was used to test the hypotheses.The empirical results indicate that twospiritual value dimensions were generated: the sense of community and well-being, and meaningful of work and values alignment.The results suggest that SVW is highly adapted in the financial sector, and the SVW measure was found to be a signiï¬cant positive and moderate correlation with the LO, HRP and OH. Although the outcomes lend support to the extended SVW model, the results are derived based on cross-sectional and the object is limited to the financial sector. Theoretical and practical implications are discussed. Keywords: spiritual values at work, learning orientation, HR Practices, organizational health JEL Classiï¬cations: D23, L20, O15